2023
DOI: 10.1021/acs.inorgchem.3c01540
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline Li2Sn(IO3)6 Microwires: Combining Optical-Waveguiding and Frequency-Doubling Functions

Abstract: High-quality single-crystalline Li2Sn(IO3)6 microwires (MWs) have been successfully prepared by using a facile hydrothermal method. The as-synthesized Li2Sn(IO3)6 MWs exhibit regular hexagonal prism morphology, excellent surface smoothness, and remarkable diameter uniformity. The optical propagation loss has been determined to be as low as 0.026 dB μm–1 at 785 nm wavelength, implying the low-loss optical waveguiding capability of the Li2Sn(IO3)6 MWs. The effective frequency-doubling conversions of the fundamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…In general, the macroscopic crystal structure is determined by the fundamental motifs that construct the crystal. The functional building blocks (FBBs) used to construct NCS crystals mainly contain the following categories: (i) planar anionic groups with a π-conjugated system, including NO 3 – , CO 3 2– , BO 3 3– , and B 3 O 6 3– ; (ii) d 0 transition metal (TM) cations with second-order Jahn–Teller (SOJT) distortion, such as V 5+ , Nb 5+ , Ta 5+ , Mo 6+ , and W 6+ ; (iii) cations with stereochemically active lone electron pair, e.g., Pb 2+ , Bi 3+ , Se 4+ , Te 4+ , I 5+ , etc. …”
Section: Introductionmentioning
confidence: 99%